High performance surface-enhanced Raman scattering from molecular imprinting polymer capsulated silver spheres1. Issue 33 (7th September 2015) - Guo, Yan; Kang, Leilei; Chen, Shaona; Li, Xin
<x xml:space="preserve">Abstract</x> Driven by the ultrasensitivity of the surface-enhanced Raman scattering (SERS) technique and the directive selection of molecular imprinting polymers (MIPs), core–shell silver-molecularly imprinted polymer (Ag@MIP) hybrid structure was synthesized to serve as a novel SERS platform.